Health and Wellbeing of India's Young People Challenges and Prospects - Bharat, Shalini; Sethi, Geeta (Springer Nature Singapore : Imprint: Springer, 2019)
This volume fills a major gap in the evidence base on adolescents and youth in India by bringing together research, policy critiques and programme analyses in an intersectoral and multidisciplinary way. With about 373 million persons between the ages of 10 and 24 years, India has the largest number of young people of any country in the world. While this large cohort presents an excellent opportunity to reap a rich demographic dividend, their potential can be realised only with intelligent investments, which create well nourished, healthy, appropriately educated and skilled youth. This volume is based on desk reviews and is complemented by discussions with experts in 4 key thematic areas: nutrition, sexual and reproductive health, mental health and livelihoods, overall focusing on the health and wellbeing of the young in India. Each chapter provides a comprehensive picture of the current situation in a focal theme and identifies significant gaps in information/data and programmes. In addition, it explores the scenario of building capacity for undertaking research on, and with adolescents, through a qualitative needs assessment. This timely volume provides a thorough overview of related research, policy and programmes for a wide group of social and behavioural scientists and public health experts interested in India's young people. .